Terceirização e indicadores de desempenho: proposta de modelo diagnóstico para uma empresa pública - Morais, Marcos Vinicius Lopes (2024)
Outsourcing is an increasingly applied practice in the public sector, aimed at improving efficiency and reducing operational costs. However, for this practice to be effective, proper monitoring of the performance of outsourced services is essential, ensuring quality and alignment with the organization’s strategic objectives. This work aims to develop an action plan based on a diagnostic model for performance evaluation, anchored in the outsourcing lifecycle of a state-owned company in the information technology sector. The approach used is a qualiquantitative one, combining bibliographic research with questionnaire application. To structure the diagnostic model of performance indicators, a theoretical model was proposed based on bibliographic research in scientific article databases and other relevant sources on the topic, identifying the most suitable indicators for each stage of the outsourcing lifecycle. To identify the main challenges and needs related to outsourcing, a questionnaire was applied. After quantifying and organizing the indicators in a diagnostic model, they were converted into an action plan format, focusing on the critical points in the outsourcing process that required intervention and improvement. The results of this study demonstrated that, through the application of the proposed instrument, it was possible to identify elements and areas for improvement which, supported by adequate monitoring, are recommended to increase the performance of outsourced services throughout the outsourcing lifecycle. The replication of this instrument provides an important foundation for evaluating operational efficiency, the quality of outsourced services provided, and the achievement of the organization’s strategic objectives within this context.